Association between time in range, a novel measurement of glycemic control and islet secretory function in chinese patients with type 2 diabetes mellitus—An observational study. (March 2021) - Xu, Shao-ying; KeLi,; Zhang, Zhen; Liu, Chun-yan; Guo, Qing-yu; Lu, Bin; Gu, Ping; Shao, Jia-qing
Abstract: Aims: To explore the association between dynamic islet secretory function and TIR (time in range), a new valuable metric of glycemic control in type 2 diabetes (T2D). Methods: In this observational study 256 patients with type 2 diabetes were included and continuous glucose monitoring system (CGMS) were applied to monitor blood glucose and also the calculation of TIR [the time spent in an individual's target glucose range (usually 3.9–10 mmol/L)]. The participants were divided into 3 groups according to the tertiles of TIR, 85 cases with TIR ≥ 65.05% (T1 group), 86 cases with 41.84 < TIR ≤ 65.05% (T2 group) and 85 cases with TIR < 41.84% (T3 group). Serum glucagon (GLA0h, GLA0.5h, GLA1h, GLA2h, GLA3h ), C-peptide (Cp0h, Cp0.5h, Cp1h, Cp2h, Cp3h ) concentration at different time points were measured after a 100 g standard steamed buns meal test to assess the pancreatic alpha cell and beta cell function. Spearman correlation analysis and multivariate linear stepwise regression analysis were adopted for statistical analysis. Results: The average age and diabetes duration of all the participants were separately 56.09 ± 13.8 years and 8.0 (4.0, 15.0) years. Compared with patients in T1 group, participants in group T2 and T3 tend to have a lower concentration of C-peptide at all time points, as well as GLA0h, GLA2h and GLA3h ( p < 0.05). TIR was positively correlated with C-peptide at different time points, area under the curve of C-peptide in half an hour (AUCCp0.5h ), GLA0h, GLA3h, area under the curve of glucagon in half an hour (AUCGLA0.5h )( rs = 0.263, 0.414, 0.510, 0.587, 0.528, 0.360, 0.259, 0.144 and 0.208, respectively, p < 0.05) and was negatively correlated with the increment of serum glucagon from baseline at 0.5 h, 1 h and 2 h after the standard energy loaded(△GLA0.5h, △GLA1h, △GLA2h )( rs = −0.152, -0.172 and −0.203, respectively, p < 0.05). Cp2h, Cp0h and GLA0h were independent factors for TIR ( β = 6.558, -6.930, 0.247, respectively, p < 0.01). Conclusion: Both islet alpha cell and beta cell secretory function have important influence on TIR, a novel vital index of glycemic fluctuation.